2014
DOI: 10.1177/1098612x14528192
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of inappropriate antidiuretic hormone secretion in a cat with a putative Rathke’s cleft cyst

Abstract: An 11-year-old spayed female domestic shorthair cat was evaluated for anorexia, lethargy and weight loss of 6 days' duration. Bilateral mydriasis, absent menace response, slow-to-absent pupillary light reflexes, bilateral retinal detachment, intermittent horizontal nystagmus, intermittent ventral strabismus and systemic hypertension were present. Biochemical analysis revealed severe hyponatremia, severe hypochloremia and mild hypokalemia. Multifocal central nervous system disease was suspected based on optic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…First, MRI strongly indicated that the intrasellar component of the lesion was etiologically associated with the pituitary gland. Second, the features of the lesion appeared similar to those of RCCs described in human (3234) and veterinary (31) medicine. In addition, although we performed cytological analysis only after the surgery (which involved removal of the hypophysis), the findings did not exclude a neuroendocrine origin.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…First, MRI strongly indicated that the intrasellar component of the lesion was etiologically associated with the pituitary gland. Second, the features of the lesion appeared similar to those of RCCs described in human (3234) and veterinary (31) medicine. In addition, although we performed cytological analysis only after the surgery (which involved removal of the hypophysis), the findings did not exclude a neuroendocrine origin.…”
Section: Discussionsupporting
confidence: 63%
“…In the present report, we describe a suprapituitary ependymal cyst that was treated by endoscopic transsphenoidal surgery in a mixed-breed dog. Current literature pertaining to veterinary medicine does not document any cases involving such lesions in dogs, although one study has described Rathke's cleft cyst (RCC) secreting antidiuretic hormone in a cat (31). In human medicine, RCCs are benign lesions that arise within the sella, between the anterior and posterior lobes of the pituitary gland, and can compress the surrounding structures of the sella turcica (optic chiasm and pituitary gland); RCCs are incidentally detected in 4–33% human autopsies (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Clinical syndromes associated with these malformations include dwarfism and aggressive behavior in dogs, and syn drome of inappropriate ADH secretion in one cat. [35][36][37][38] This is the first report of a pituitary cyst resulting in adipsic CDI in the veterinary literature.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly cited causes include the administration of fluids poor in Cl -(e. g. sodium bicarbonate) and chronic respiratory acidosis. Feline hypochloremia has also been reported in many diseases in cluding kidney disease (17,18), acute tumor lysis syndrome (5), anemia (11), urethral obstruction (26), diabetes mellitus (4,7,8,37), metabolic alkalosis (22), systemic inflammatory response (9), hyperadrenocorticism (36), hyperaldosteronism (12), hypoadrenocorticism (30), acute congestive heart failure (21), refeeding syndrome (3) and syndrome of inappropriate antidiuretic hormone secretion (10). Although the application of a correction formula (Clcorrected = Clmeasured × Na + normal / Na + measured ) is important to exclude low plasma Clconcentrations caused by Cl --dilution e.g.…”
Section: Introductionmentioning
confidence: 99%